2009
DOI: 10.1063/1.3153350
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of solvent effects on the coil-globule transition

Abstract: The coil-globule transition of a polymer in a solvent has been studied using Monte Carlo simulations of a single chain subject to intramolecular interactions as well as a solvent-mediated effective potential. This solvation potential was calculated using several different theoretical approaches for two simple polymer/solvent models, each employing hard-sphere chains and hard-sphere solvent particles as well as attractive square-well potentials between some interaction sites. For each model, collapse is driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…21,22 Solvent induced polymer chain collapse and/or precipitation can be a) taylormp@hiram.edu realized in these simple chain-in-solvent systems by varying the solvent-polymer interaction potential. [23][24][25][26][27][28][29] A rigorous statistical mechanical treatment of the coupling between the local structure of a polymer and its immediate environment is a difficult many-body problem. 12,30 This problem is often avoided when studying a polymer chain in dilute solution by treating the solvent implicitly as a continuum whose average effects are accounted for by an effective polymer site-site interaction potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Solvent induced polymer chain collapse and/or precipitation can be a) taylormp@hiram.edu realized in these simple chain-in-solvent systems by varying the solvent-polymer interaction potential. [23][24][25][26][27][28][29] A rigorous statistical mechanical treatment of the coupling between the local structure of a polymer and its immediate environment is a difficult many-body problem. 12,30 This problem is often avoided when studying a polymer chain in dilute solution by treating the solvent implicitly as a continuum whose average effects are accounted for by an effective polymer site-site interaction potential.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, more recent work by Polson et al suggests that Grayce's approach breaks down for longer chains and at high solvent density. 28 In general, such multi-body potentials are difficult to work with, and thus, this exact approach does not necessarily simplify the problem. By introducing the approximation of pairwise additivity for the exact n-body solvation potential, we can significantly simplify the chain-in-solvent problem, reducing it to a single n-mer chain self-interacting via a set of (at most) n(n − 1)/2 effective site-site potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The coil‐globule transition can be influenced or induced by various factors,1–11 such as confinement, chain stiffness, hydrogen bond, and hydrodynamic interactions. Excellent studies on theories, experiments, and simulations can be found everywhere 12, 13. Additionally, there are two classical polymer physics books14, 15 where more details can be found.…”
Section: Introductionmentioning
confidence: 99%
“…In both the SW and LJ systems, one can drive chain collapse in a dense, low temperature solvent environment by simply reducing the attractive part of the chain-solvent interaction (leaving the solvent-solvent and intramolecular chain-chain interactions unchanged). 17,[23][24][25][26][27][28] This change reduces the solvating power of the solvent and allows for a continuous tuning of solvent conditions from good to poor.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, Polson et al have recently shown that Grayce's approximate many-body approach fails for longer chains at high solvent density. 28 We have recently investigated the validity of the pair decomposition approximation for both short HS and SW chains in monomeric HS and SW solvent, respectively. 17 Our "numerically exact" results show that while a single two-site solvation potential is unable to capture the complete effects of solvent, a set of two-site solvation potentials can exactly map the chain-in-solvent problem onto that of an isolated chain.…”
Section: Introductionmentioning
confidence: 99%